2013
DOI: 10.4108/el.1.3.e3
|View full text |Cite
|
Sign up to set email alerts
|

A study of the effects of computer animation on college students’ learning of Leadership in Energy and Environmental Design - LEED

Abstract: This paper presents ongoing research aimed at investigating the efficacy of computer animations in improving college students' learning of building sustainability concepts and practices. The use of animations in educational contexts is not new, however scientific evidence that supports their effectiveness as educational materials is still limited. This paper reports an experiment that explored the impact of an educational digital animation, called "LEED-ERS", on college students' learning of Leadership in Ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Buildings are one of the main consumers of energy [9][10][11]. According to building sector, in the US and UK buildings use 45% and 42% of the entire energy countrywide, while in OECD countries the corresponding share is 31% [1].…”
Section: Introductionmentioning
confidence: 99%
“…Buildings are one of the main consumers of energy [9][10][11]. According to building sector, in the US and UK buildings use 45% and 42% of the entire energy countrywide, while in OECD countries the corresponding share is 31% [1].…”
Section: Introductionmentioning
confidence: 99%
“…Our growing awareness of these problems has made sustainable development a priority as it represents an important way to mitigate some of the most serious environmental impacts of industrialization [5,6]. The construction industry is a significant consumer of energy and raw materials and is thus a major contributor to global warming [7][8][9][10][11]. Several previous studies have indicated that globally, the construction industry consumes~50% of the energy produced, nearly 40% of the raw materials, and 16% of the water, and is responsible for 35 % of the CO 2 produced [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have studied the influence of computer animations on students' learning through various experiments and have achieved conflicting results. Although some experiments demonstrate the efficacy of animation as a learning tool (Dooley et al, 2000;English and Rainwater, 2006;Wilson and Dwyer, 2001;Nilforooshan et al, 2013), other studies suggest that animations can be distracting with little or no positive effect on learning (McGregor et al, 2003;Park and Hopkins, 1993).…”
Section: Computer Animations and Students' Learningmentioning
confidence: 99%